Розробка системи електропостачання ВАТ «Одеський завод сільськогосподарського машинобудування» - Антибура, Тимофій Миколайович; Antybura, Tymofii (ЦНТУ, 2025)
В кваліфікаційній роботі виконано розробку системи електропостачання ВАТ «Одеський завод сільськогосподарського машинобудування» згідно завдання. В роботі предоставлений огляд існуючих рішень, вибрано обладнання та принцип його роботи, розроблена система електропостачання та вибране необхідне обладнання. В спеціальному розділі розроблено автоматизовану систему обліку електричної енергії. In the qualification work, the development of the power supply system of OJSC "Odessa Agricultural Machinery Plant" was carried out according to the task. The work includes an overview of existing solutions, selection of equipment and description of its operation principles, development of the power supply system, and selection of the necessary equipment. A dedicated section is devoted to the development of an automated system for electricity metering and control.
Development of a power supply system for Odesa Agricultural Engineering Plant OJSC
Keywords: електропостачання; АСКОЕ; електричні навантаження; прилади обліку; power supply; SCADA; electrical loads; metering devices